ON THE SPECTRAL THEOREM FOR A BANACH REPRESENTATION OF A COMPACT GROUP GENERATED BY DELSARTE SHIFTS - Karakhanian, M. I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
This paper is devoted to the spectral theorem for a Banach representation of a compact group G in a Banach space X generated by Delsarte shifts.